2011
DOI: 10.5336/medsci.2010-20628
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of M694V Mutation on Clinical Presentation and Acute Phase Response in Children with Familial Mediterranean Fever: Single Center Experience in Western Turkey

Abstract: A AB BS S T TR RA AC CT T O Ob b j je ec c t ti i v ve e: : The aim of this study was to in ves ti ga te the phe noty pe-ge noty pe cor re la tion and the re la ti ons hip bet we en cli ni cal se ve rity sco re and acu te pha se res pon se in chil dren with fa mi li al Me di ter ra ne an fe ver (FMF) in Wes tern Tur key. M Ma a t te e r ri i a al l a an nd d M Me et t h ho od ds s: : The me di cal records of 87 FMF chil dren (me an age: 11.1 ± 3.6 ye ars; ran ge: 3-20 ye ars; me an age at di ag no sis: 8.3 ± 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Another study showed that FMF children with M694V homozygote genotype were associated with a higher acute phase response during FMF attacks and severe clinical symptoms [19]. It should be noted that both studies reported the acute phase reactant levels either during the attack free period or the attack-periods and not at the time of diagnosis like what we did in this paper.…”
Section: Discussionsupporting
confidence: 68%
“…Another study showed that FMF children with M694V homozygote genotype were associated with a higher acute phase response during FMF attacks and severe clinical symptoms [19]. It should be noted that both studies reported the acute phase reactant levels either during the attack free period or the attack-periods and not at the time of diagnosis like what we did in this paper.…”
Section: Discussionsupporting
confidence: 68%